The relationship between training load and neuromuscular control in adolescent female basketball athletes - Beltz, E. M.; Denegar, C. R.; Burland, J. P.; Huggins, R. A.; Lepley, L. K.; DiStefano L. J. (Journal of Athletic Training, 2019)
Context: Training load (TL) is proposed to infl uence injury risk by altering modifi able risk factors. Neuromuscular control (NMC) is a known risk factor for injury that is modulated by other intrinsic factors, such as fatigue. While both NMC and TL are independently related to musculoskeletal injury risk, the relationship between NMC and TL remains unclear. Therefore, the purpose of this study was to evaluate the relationship between NMC and TL in adolescent female basketball players. Methods: Observational,cohortfi eld study. Twenty female basketball athletes (15.6 ± 1.4 years, 168.0 ±7.4 cm, 59.5 ± 8.5 kg)at two high schools volunteered for this study. NMC was assessed at three time points (PRE, MID, POST) over a single athletic season using a standardized jump-landing task and the Star Excursion Balance Test (SEBT). For the jump-landing task, participants jumped forward off a 30 cm-high box to a distance approximately half their height and immediately performed a maximal vertical jump upon landing. The jump-landing task was videotaped from sagittal and frontal views and graded at a later date by a blinded single-rater using the Landing Error Scoring System (LESS). TL was estimated using Session RPE (sRPE), which is the product of the CR-10 Rating of Perceived Exertion and minutes of physical activity, which were self-reported daily. The average LESS score for three jump-landings was used for analyses. A composite SEBT score, normalized to limb length, was calculated. Reach distances for individual SEBT directions (anterior [ANT], posteromedial [PM], posterolateral [PL]) were calculated using the maximum distance. The absolute bilateral difference in anterior reach distance (R-L ANT), which has been shown to be predictive of lower extremity injury in high school basketball athletes, was also calculated. Total sRPE over the previous 7 (sRPE7) and 28 days (sRPE28), and acute:chronic sRPE, were calculated. Bivariate, bootstrapped correlations (1000 samples) were used to evaluate associations between TL (sRPE the day prior, sRPE7, sRPE28, acute:chronic sRPE) and NMC (LESS, SEBT, individual reach distances, R-L ANT) variables. a<0.05. Results: R-L ANT reach distance was negatively correlated with sRPE7 (p=0.03, r=-0.40, 95%CI [-0.67, 0.01]) and acute:chronic sRPE (p=0.03, r=-0.38, 95%CI [-0.63, -0.07]) (Table 1). There were no other signifi cant correlations between TL and NMC variables (p>0.05). Conclusions: R-L ANT was negatively associated with measures of training load, suggesting that as loads increased there was a decrease in theoretical injury risk. These data do not support epidemiological evidence that indicates an increase in injury incidence with increasing workloads. There may be a threshold above which TL impairs NMC, and this threshold may not have been reached in many or all of the participants in this study. Additional research regarding the relationship between NMC and TL is warranted, specifi cally to understand thresholds at which increases in TL impair NMC across subpopulations of athletes.